2022
DOI: 10.3390/su141912911
|View full text |Cite
|
Sign up to set email alerts
|

Can Proximal Environments Prevent Social Inequalities Amongst People of All Ages and Abilities? An Integrative Literature Review Approach

Abstract: Although many studies are currently examining the city of proximity as a way to promote sustainable and environmentally friendly cities, few consider it meaningful to achieve an “inclusive” mobility model for people of all ages and abilities, including people with disabilities, children, or the elderly. This literature review paper focuses on the extent to which the city of proximity can provide inclusive mobility and reduce inequalities in the urban scene, thus achieving social sustainability. Out of the 256 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 120 publications
0
3
0
Order By: Relevance
“…As a result, efficient and well-designed PT facilitates the accommodation of different ways of meeting their needs. From this perspective, PT improves equal access to opportunity [45,46].…”
Section: Inequitable Access To Ptmentioning
confidence: 99%
“…As a result, efficient and well-designed PT facilitates the accommodation of different ways of meeting their needs. From this perspective, PT improves equal access to opportunity [45,46].…”
Section: Inequitable Access To Ptmentioning
confidence: 99%
“…From the socio-ecological model [17], the physical environment would be relevant for the levels and type of physical activity taking place in a city, neighborhood, or community [18]. Different studies have found that proximity to an exercise facility is positively associated with leisure-time physical activity, whether considering proximity as a 10 min walking distance, 1 km from home, "the 15-min city", a 20-min walking distance, or even asking about perceived proximity [19][20][21][22][23][24][25]. In adults, PA among women, younger adults, people with higher education, and urban residents appeared to have a stronger association with distance to an exercise facility [19].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents' perception of living in environments or dwellings that facilitate physical activity is associated with a healthier BMI, more hours of physical activity and family time, and fewer hours of screen time [20], as well as greater intensity and duration of PA activities [24]. Regarding children, there is a significant correlation between the spatial characteristics of an urban neighborhood and general environmental cues regarding the duration and intensity of physical activity [21].…”
Section: Introductionmentioning
confidence: 99%